Method for producing decorative element comprising engineered stone and decorative element
By using inkjet printing technology and vacuum vibration compaction technology in the manufacturing process of engineering stone decorative components, the problem of difficult to obtain replicable and predetermined decoration in the prior art is solved, and efficient and environmentally friendly engineering stone decorative components are achieved. Production.
Patent Information
- Application Number
- CN202380050256.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-15
- Filing Date
- 2023-06-27
- Publication Date
- 2025-02-21
AI Technical Summary
Prior Art When manufacturing engineered stone decorative elements, it is difficult to obtain products with replicable and predetermined decorations, and traditional methods have problems of environmental impact and high cost.
By providing a mixture containing inorganic filler and adhesive, compacted and cured to obtain a substrate, followed by inkjet printing decorative patterns on the top surface of the substrate, combining vacuum and vibration compaction techniques to reduce porosity and improve surface finish.
The manufacture of engineered stone decorative components with high resolution and replicable decorative patterns is realized, reducing production costs and improving environmental protection.
Smart Images

Figure CN119497705A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a decorative element comprising engineered stone and a decorative element comprising engineered stone. The decorative element of the present invention is of the type comprising a base and a top layer, wherein the base is made of engineered stone and wherein the top layer comprises a decorative pattern. In particular, the engineered stone of the present invention is generally known as quartz on the market. Background Art
[0002] Engineered stone includes inorganic fillers such as crushed stone, sand or other minerals, but also recycled ceramics or glass bonded by a curing resin. In more detail, engineered stone refers to a composite material formed by inorganic fillers or stone materials bonded together by a curing binder that cures at low temperatures, where low temperatures refer to temperatures below 500° C. The binder is preferably a thermosetting resin.
[0003] Natural stone has traditionally been used as a building material, especially for finishing buildings, for example for wall or floor coverings, and for the production of worktops, such as kitchen or bathroom countertops and vanities. Natural stone is extracted from mines and subsequently cut and polished to obtain slabs or plates with the desired shape. Due to the mining process, natural stone is relatively expensive and has a high impact on the environment.
[0004] Therefore, in the last few years, in order to reduce costs and provide a more environmentally friendly product, methods for manufacturing engineered stone have been developed. For example, the so-called The technology represents a well-known example of such a method. The document discloses a method for manufacturing an engineered stone, comprising the following steps: providing a mineral filler, for example by grinding sand or quartz; mixing a stone or stone-like material with a binder (for example, a resin powder) to obtain a mixture; depositing the mixture in a mold of a press, the mold having a shape and size similar to the final product; applying a vacuum to extrude the mixture while applying a vibration motion at a predetermined frequency; then hardening the obtained semi-finished product by a thermal curing process to obtain the engineered stone; then subjecting the engineered stone to a finishing step, such as cutting or polishing.
[0005] Such engineered stones usually comprise a monochromatic decoration. Alternatively, the engineered stone comprises a decoration comprising an artificial texture for imitating natural stone, such as marble or granite. Such a decoration is obtained by adding a colorant to the mixture before it is deposited in the mold, as disclosed in WO 2009 / 010406. The mixture is carried by an endless belt above the mold and loaded into the mold itself by free falling from the end of the belt. The colorant is loaded onto the surface of the mixture substantially corresponding to the end of the belt through an appropriate nozzle, thereby falling into the mold with the mixture in an uncontrolled manner. After the vibration compression step, the pigment particles are distributed in the mixture, thereby producing a texture effect over the entire thickness of the engineered stone. Therefore, it is not possible to obtain an engineered stone with a reproducible and predetermined decoration using this technology.
[0006] WO 2016 / 113652 discloses an apparatus and method for producing programmable color effects in engineered stone by means of a computer-controlled machine. The machine is a humanoid robot or a rectangular coordinate type robot provided with one or more nozzles for dispensing colorants into grooves formed in a mixture in a temporary support. The nozzles are connected to a tool that interacts with the surface of the mixture to produce grooves or holes to receive the color, thereby simulating the marble texture. The apparatus therefore requires mechanical processing of the mixture and provides a decoration simulating natural stone with a relatively low quality resolution. The technique is slow and has limitations in terms of the size of the simulated texture that can be simulated. In addition, care should be taken to vibrate and compact the pattern produced so that the final pattern is always different from the initial predetermined pattern.
[0007] WO2019070621 discloses a method for improving the aesthetic quality of engineered stone by inkjet printing a decoration on a major surface of the stone. Summary of the invention
[0008] The object of the present invention is firstly to provide an alternative and improved method for manufacturing engineered stone which, according to several of its preferred embodiments, aims to solve one or more of the problems arising in the prior art.
[0009] Furthermore, according to a first independent aspect of the present invention, the present invention relates to a method for manufacturing a decorative element comprising a base and a top layer, wherein the base is made of engineered stone and wherein the top layer comprises a decorative pattern, the method comprising the following steps:
[0010] - providing a mixture comprising at least an inorganic filler and a binder;
[0011] - compacting the mixture;
[0012] - curing the adhesive to obtain a substrate;
[0013] And wherein the method comprises the step of inkjet printing a first decorative pattern on at least the top surface of the substrate.
[0014] Engineered stone can be manufactured in any desired form, although a substantially flat shape, such as a board, tile or slab is preferred. Engineered stone is preferably shaped as a slab, wherein the slab is intended to be in a generally rectangular and flat form, preferably comprising a minimum surface of 1.5 square meters. In this way, engineered stone is manufactured in a sufficiently large shape to have versatility and is suitable for cutting according to the size and shape of the final destination of the engineered stone itself, such as a kitchen or bathroom countertop. According to a preferred embodiment, the slab has a length of at least 2m, preferably at least 2.5m, such as 3m or more, and a width of at least 1m, preferably 1.5m or more. In addition, the slab preferably shows a thickness of at least 10mm, preferably at least 20mm, such as 30mm.
[0015] In a preferred embodiment, the inorganic filler comprises a mineral material, such as any kind of stone, sand, silicon mineral material, such as quartz, silica sand, clay, feldspar, cristobalite, granite, talc or calcium mineral material, such as calcium carbonate, marble, gypsum. The inorganic filler can also include ceramics, glass, metal and other inorganic materials, such as recycled materials. The filler can be in the form of powder, granule, fragment, grain, aggregate or any other particulate, although preferably in the form of granules and powders. Preferably, the filler is a powder form with an average particle size of less than 45 μm, preferably less than 20 μm. The filler is preferably at least 80% by weight of the mixture, preferably greater than 85%, and more preferably greater than 90%. According to another embodiment of the present invention, the filler can be in the form of aggregates, grains and / or particles with a particle size distribution between 0.1 and 6.5 mm, preferably between 0.1 and 2 mm, between 0.1 and 0.7 mm. In a most preferred embodiment, the filler consists of a combination of powders and granules, for example the combination may contain at least 60 wt% of granules and / or particles and between 20 and 35 wt% of powder form, wherein (for example) the particles have a particle size distribution between 0.1 and 6.5 mm, and the powder has an average particle size of less than 45 μm, preferably less than 20 μm. In a most preferred embodiment of the present invention, the majority of the filler, i.e. at least 50 wt%, and more preferably mainly consists of inorganic materials based on silicon (Si). Silicon-based materials, such as silicon minerals and glass, show good affinity with adhesives, thereby improving the final bonding.
[0016] In some embodiments, crystalline silica, feldspar or kaolin may constitute the preferred choice of inorganic filler or at least the majority of filler because they may appear relatively white. In some embodiments, glassy and / or amorphous inorganic fillers may be preferred for forming the majority of inorganic filler because they may reduce the amount of free crystalline silica dust in the manufacture and / or processing of decorative elements.
[0017] Binder is a curable substance configured to cure, thereby bonding particles of stone or stone-like material together. The binder can be in any form, i.e., liquid, solid, gel, or any form suitable for mixing with the filler and uniformly dispersing therein. In some embodiments, a powder form may be preferred because it reduces the possibility of contamination of the mixture by other substances, which may occur when using a wet form of the binder. The binder may be an organic substance, such as a resin. In the most preferred embodiment, the binder may be a thermosetting resin.
[0018] In a most preferred embodiment, the binder comprises, preferably consists essentially of, a polyester resin, preferably an unsaturated polyester resin. Less preferred alternatives for binders include acrylic resins, epoxy resins, polyurethanes, rubbers, vinyl ester resins, and the like. The binder is preferably less than 20%, preferably less than 15%, and more preferably less than 10% by weight of the mixture. Polyester resins have shown very high coupling capabilities with inorganic fillers.
[0019] It should be noted that the mixture may also contain additives, such as coupling agents, catalysts or agents to activate or accelerate the hardening of the adhesive, and / or temporary binders, such as glue or thermoplastic resins for temporary bonding of stone or stone-like materials. In the most preferred embodiment, the additives include at least one silane-based coupling agent to further enhance the bond between the silicon-based filler and the adhesive, preferably an unsaturated polyester adhesive. In addition, the additives may include crosslinking agents and / or catalysts to activate and / or accelerate the curing of the adhesive.
[0020] In a preferred embodiment, the mixture may further comprise one or more colorants. The colorant may be in the form of a dye or a pigment. Pigments are generally preferred because they provide better UV resistance to the final engineered stone. The pigment may be organic or inorganic, the latter being even more preferred because UV resistance is further improved. Preferred colors of the colorant are black, yellow, white, red and green.
[0021] The mixture may be provided in different forms, such as in the form of a pasty material or slip, although a dry form, such as loose particles, is preferred. According to a preferred embodiment wherein the mixture is provided in the form of a loose material, the mixture comprises first particles of filler and second particles of binder mixed together, the mixture preferably being in the form of a powder. Alternatively, the loose particles may be formed of granules or pellets, wherein each particle comprises a filler and a binder bonded together to form a particle.
[0022] In a preferred embodiment, the mixture may be provided through a hopper or feeder directly into a mold, a frame or any other tool suitable for shaping the mixture.
[0023] Before and / or during the step of providing the mixture into the mold, a first colorant or a first colorant group may be added to the mixture. The first colorant or a first colorant group may be evenly distributed in the substrate to provide the basic color of the engineered stone. In some embodiments, the first colorant or a first colorant group may be distributed according to a random pattern, such as a random texture effect or a dotted effect.
[0024] During and / or after the step of providing the mixture into the mold, a second colorant or a second colorant group can be added to the mixture in the mold according to a pattern that can be random or predetermined. Preferably, the second colorant or a second colorant group can be provided according to a predetermined pattern, such as a texture effect that imitates the texture or scales of marble, granite or any natural stone. In a preferred embodiment, a computer-controlled machine, such as a humanoid robot or a rectangular coordinate robot, can be used to form a predetermined pattern, and the machine is provided with one or more nozzles for dispensing colorants. The nozzle is connected to a tool that interacts with the surface of the mixture to produce grooves or holes to receive the colorant. Preferably, the predetermined pattern is obtained using computer-controlled machines such as those described in WO 2016 / 113652.
[0025] The random pattern formed by the first colorant or the first colorant group, or the predetermined pattern formed by the second colorant or the second colorant group, or preferably a combination thereof, forms a second decorative pattern of the decorative element. The second decorative pattern is present in the substrate and in particular over the entire thickness of the substrate. In fact, the second decorative pattern forms a three-dimensional decoration.
[0026] The mould may have shapes and dimensions similar to those of the final product to be obtained or those of the semi-finished product of the method. Preferably, the mould or frame has shapes and dimensions similar to those of a slab or panel. In a preferred embodiment, the mould is made of rubber and comprises a concave body suitable for receiving the mixture and a cover suitable for closing the concave body so that the mixture is completely enclosed in the mould. It should be noted that in less preferred embodiments, the mixture may be arranged only on a belt or in an open mould or frame.
[0027] Preferably, the compaction step is carried out under vacuum, i.e. a vacuum is created in the mould to help extract the air between the particles of the mixture. More preferably, vibrations are applied to the mould or frame during the compaction step, thereby helping the particles of the mixture to compact, so that the porosity of the engineered stone is significantly reduced. According to a preferred embodiment, both vacuum and vibrations are applied to the mixture during compression. In this way, it is possible to obtain a very high degree of compaction of the mixture, which will result in a very low porosity after curing.
[0028] It should be noted that due to the compaction step, the powders and granules forming the mixture in the mold can be displaced, which changes the pattern of the first and / or second coloring agent. Therefore, the final second decorative pattern of the decorative element is different from the pattern initially provided to the mold, and each decorative element is unique and different from each other. In particular, the vibrations can cause the particles to be displaced, so that there can be a mixture of colors and / or a mixture of colored and colorless mixtures. For example, in the case where such a displacement occurs at the edge of the texture forming the second decorative pattern, this can lead to the creation of a shading at the edge itself, making the outline of the texture less clear.
[0029] After the compaction step, the mixture in the mold is transported to a curing station. The curing of the adhesive can be achieved by radiation, heat, chemical curing or other suitable techniques. In a preferred embodiment, the curing step is carried out at a temperature below 500° C., such as below 200° C., such as at room temperature. In particular, in a preferred embodiment, the curing step can be heat-activated and continue in an exothermic reaction. The activation of the curing of the adhesive can occur at a temperature below 100° C.
[0030] After curing, the engineered stone comprises a porosity of less than 1% by volume, more preferably less than 0.5% by volume, even more preferably less than 0.2% by volume.
[0031] After curing, the engineered stone is removed from the mold. In some embodiments, the engineered stone is cooled and / or conditioned before proceeding to the next step.
[0032] After curing, the method may comprise a calibration step and / or a squaring step. Calibration and squaring are machining steps whose scope is to provide the engineered stone with the final desired shape and size. In particular, calibration has the scope of leveling one or both of the main surfaces of the substrate made of engineered stone.
[0033] The method may also include at least mechanical surface treatment of the upper surface of the substrate to provide the desired texture to the latter. The mechanical surface treatment may be a polishing, grinding or grinding (sanding) step. In a preferred embodiment, the polishing step is carried out using a CAMI particle size number between 300 and 600 grit, preferably an abrasive of 400 grit. The inventor has found that the polishing step carried out in this way can provide improved bonding between the substrate and the top layer of the decorative element. In fact, the texture obtained is rough enough to provide an increase in specific surface, thereby overcoming the lack of adhesion caused by the low porosity of the substrate. In addition, it has been found that the roughness obtained in this polishing step using this type of grinding is ideal for optimizing the scratch resistance and gloss of the final product. It should be noted that mechanical surface treatment is more preferred than chemical surface treatment, such as etching, because chemical surface treatment is less controllable and may damage the engineered stone and / or the second decorative pattern.
[0034] After the mechanical surface treatment, the method may include the step of applying a viscosity promoter coating on the upper surface of the substrate. The viscosity promoter coating can improve the adhesion of the top layer to the substrate, thereby ultimately improving the scratch resistance of the decorative element. In the most preferred embodiment, the viscosity promoter coating may contain a silane-based substance. The viscosity promoter coating may be applied in an amount between 20 and 60 g / sqm, preferably 40 g / sqm. The viscosity promoter coating may be applied using a variety of techniques, preferably roller coating. The viscosity promoter coating is preferably transparent or translucent, so that the second decorative coating is visible through it. In the most preferred embodiment, the viscosity promoter coating is a water-based substance, and the method also includes the step of drying the viscosity promoter coating. In some embodiments, the viscosity promoter coating may contain a dry matter to water content ratio between 1:6 and 1:3, for example 1:4. Preferably, the amount of the above-mentioned viscosity promoter applied is a wet amount, for example taking into account the water content of the coating before the drying step. The drying step may be carried out using blowing hot air and / or IR radiation. Blowing hot air is preferred as it has been found to be less aggressive to the substrate which may yellow or become damaged by the high temperature after the adhesive has cured. The drying step may be carried out at a temperature between room temperature and 100°C, for example at 50°C.
[0035] Subsequently, the method according to the invention may comprise the step of applying a primer coating on the upper surface of the substrate, in particular on top of the viscosity promoter coating. The primer coating may be suitable for making the substrate surface suitable for receiving ink. In fact, the substrate is substantially non-porous and the ink will tend to bleed, with a consequent reduction in resolution. Due to the primer, it is possible to obtain a good fixation of the ink, thereby improving the scratch resistance and the high resolution of the first decorative pattern. In a most preferred embodiment, the primer coating is transparent or translucent, so that the second decorative coating is visible through the primer coating itself, and the final aspect of the upper surface of the decorative element is formed by the combination of the first aspect and the second aspect.
[0036] It should be noted that in some alternative embodiments, a viscosity promoter coating and / or a primer may be provided immediately after the calibration step, or even without said mechanical surface treatment after the calibration step. This is particularly the case when a subsequent polishing step is performed.
[0037] It should also be noted that the fact that the method comprises the step of providing a viscosity promoter coating on the substrate surface forms an inventive aspect of the solution, which aspect may be independent of any other feature or embodiment described herein. It is further clear that this second independent aspect related to the application of a viscosity promoter coating may be combined with any other feature or embodiment described herein.
[0038] In the most preferred embodiment, the primer coating can be a radiation curable material, preferably a UV or EB curable material. Radiation curing is more preferred than thermal curing because it can reduce the risk of yellowing or damage to the engineered stone. Preferably, the primer coating is acrylate-based. Possible preferred examples of primer coatings can include acrylate-based oligomers, such as epoxy acrylates, polyester acrylates, polyurethane acrylates. Other examples of acrylate-based primer coatings can include acrylate-based monomers, preferably acrylate-based monomers with a functionality of 1 to 6. Most preferably, the primer coating includes a UV absorber, such as a UV absorber belonging to the triazine family or the benzotriazole family. The UV absorber can reduce the yellowing of the primer coating caused by (for example) UV radiation from sunlight during the normal use of the decorative layer.
[0039] In some embodiments, the primer coating may be applied using a roller coating technique, preferably using a soft roller having a Shore hardness of less than 50 Shore, preferably between 20 and 30 Shore, for example 26 Shore. In some embodiments, the primer coating may be applied in an amount of between 5 and 75 g / sqm, more preferably between 5 and 60 g / sqm, for example 6 or 10 g / sqm. The inventors surprisingly found that when the amount of primer coating is close to the lower end of the range shown, it is possible to improve the final surface finish, in particular the gloss.
[0040] After applying the primer coating, the method includes the step of gelling or at least partially curing the primer coating itself. In the most preferred embodiment, the primer coating is gelled using a gallium UV lamp. A gallium UV lamp is preferred because it has a longer wavelength than other lamps and can penetrate deeper into the coating.
[0041] In a preferred embodiment, the first decorative pattern may be printed onto the upper surface of the substrate after applying the primer coating. The printing step may be performed to obtain a printed pattern with a resolution of up to 360 dpi. The printer may be a single pass printer or a multi-pass printer. The printing is preferably an inkjet printing step, which comprises ejecting ink drops from a print head, which may be a piezoelectric (preferably) or bubble (alternatively) print head.
[0042] It should be noted that the printed pattern may preferably be applied to the predetermined point in a fixed relationship, such that the printing is applied at a predetermined position of the substrate, for example at a fixed distance from an edge or corner, which distance may be zero, and the printed pattern is preferably aligned with the edge, preferably with the longitudinal edge of the substrate. Applying the printed pattern to the predetermined point in a fixed relationship is advantageous for obtaining at least a partial match between the first and second decorative patterns.
[0043] In a preferred embodiment, the method comprises a step of identifying a second pattern present on the substrate and a step of selecting the pattern to be printed based on said identification. In this way, it is possible to obtain at least a partial matching of the first decorative pattern and the second decorative pattern of the decorative element to provide a continuous impression from the surface to a certain thickness.
[0044] According to the present invention, the ink may preferably be a pigmented ink. The pigment may be organic or inorganic. Inorganic pigments are preferred because they provide better UV resistance. It should be noted that for black inks, the preferred pigment is carbon black. In a most preferred embodiment, the ink is a radiation curable ink, preferably a UV, EB or Hydro-UV curable ink.
[0045] Preferably, the ink comprises pigment particles having a maximum dimension of less than 2 μm, for example less than 1.5 μm, making it possible to obtain printed patterns with very high resolution. The ink may show a viscosity of less than 70 cP, preferably less than 50 cP and / or a surface tension of less than 25 dyn / cm.
[0046] It should be noted that the printed pattern can be obtained with inks of multiple colors, for example, with four colors, preferably cyan, magenta, yellow and black, or more colors, for example seven or eight colors. In any case, in a preferred embodiment, printing can be performed with only one ink, in which case the selected ink is black ink, which is particularly the case for marble decoration.
[0047] In some embodiments, the ink may be transparent or translucent, such that a second decorative pattern present in the substrate is visible through the ink, ie, at the same point where the ink has been dropped, the second decorative pattern may be at least partially visible.
[0048] The ink is preferably a UV curable ink. In particular, the ink may include a UV curable adhesive which, once cured, fixes the pigment on the surface of the decorative element. The method preferably includes a step of at least partially curing or gelling the printed ink. Preferably, the curing step is performed using an LED UV lamp.
[0049] The method further comprises the step of providing a protective coating on the printed pattern. In the most preferred embodiment, the protective coating is provided in a double layer. Preferably, a primer is applied immediately on top of the printed pattern and a top coating is provided on top of the primer.
[0050] Preferably, the primer layer is transparent or translucent. The primer layer is preferably acrylate-based. Possible preferred examples of primer layers may include acrylate-based oligomers, such as epoxy acrylates, polyester acrylates, polyurethane acrylates. Other examples of acrylate base coatings may include acrylate-based monomers, preferably with a functionality of 1 to 6. Preferably, the primer layer includes a scratch-resistant additive, such as hard particles. Preferably, the primer layer contains a UV absorber, such as a UV absorber belonging to the triazine family or the benzotriazole family, which can reduce or prevent the yellowing of the primer coating caused by (for example) UV radiation from sunlight during the normal use of the decorative layer.
[0051] Preferably, the primer layer can be applied using a roller coating technique, preferably using a soft roller with a Shore hardness of less than 50 Shore, preferably between 20 and 30 Shore, for example, 26 Shore. In some embodiments, the primer layer can be applied in an amount of between 5 and 75 g / sqm, more preferably between 5 and 60 g / sqm, for example, 6 or 50 g / sqm. The inventors unexpectedly found that when the amount of the primer layer approaches the lower limit of the range shown, it is possible to improve the final surface finish, specifically the gloss. On the other hand, it has been found that a higher amount of primer provides a better synergy with the top coat because it is easier to perform a grinding step, which will be described below. Specifically, it has been found that in an embodiment of the method in which grinding is performed after the primer layer is applied, the primer layer is preferably applied in an amount of at least 35 g / sqm. On the other hand, in an abnormal embodiment in which grinding is not performed after the primer layer is applied, the primer layer can be provided in an amount between 6 and 10 g / sqm.
[0052] The method preferably includes a step of partially, possibly completely, curing the primer layer before the step of providing the top coating. Preferably, a gallium UV lamp and / or a mercury (Hg) UV lamp may be used to cure the primer layer. In a preferred embodiment, the primer layer is completely cured, for example, using gallium and mercury (Hg) UV lamps.
[0053] After applying the base coat and at least partially, preferably completely curing, the method may preferably include mechanical surface treatment of the base coat. The mechanical surface treatment may be a polishing, grinding or grinding step. In a preferred embodiment, the method includes a desert step. This intermediate step between applying the base coat and the top coat can remove any pattern left by the roller coating, such as the orange peel effect, and achieve a smooth finish, and improve the adhesion of the top coat, thereby improving the scratch resistance of the top layer. In a most preferred embodiment, the grinding step is performed using an abrasive with a CAMI particle size number between 300 and 1000 particles. In a most preferred embodiment, the grinding step can be performed using a variety of abrasives with a CAMI particle size number gradually increasing. For example, the first abrasive can show a CAMI particle size number between 300 and 400 particles, such as 320 particles. Preferably, the first abrasive can move in a direction perpendicular to the advancing direction of the decorative element or at least inclined. For example, the second abrasive can show a CAMI particle size number between 400 and 600 particles, such as 500 particles. Preferably, the second abrasive can be moved in a direction substantially parallel to the direction of advancement of the decorative element. For example, the third abrasive can show a CAMI grit number between 500 and 700 grit, for example 600 grit. Preferably, the third abrasive can be moved in a direction perpendicular to or at least oblique to the direction of advancement of the decorative element. For example, the fourth abrasive can show a CAMI grit number between 600 and 1000 grit, for example 800 grit. Preferably, the fourth abrasive can be moved in a direction substantially parallel to the direction of advancement of the decorative element. It has been found that the texture of the base coat obtained in this sanding step using these kinds of abrasives is ideal for optimizing the scratch resistance and gloss of the final product.
[0054] The top coating layer may be transparent or translucent. The top coating layer may preferably be acrylate-based. Possible preferred examples of the top coating layer may include acrylate-based oligomers, such as epoxy acrylates, polyester acrylates, polyurethane acrylates. Other examples of acrylate-based top coating layers may include acrylate-based monomers, preferably with a functionality of 1 to 6. Preferably, the top coating layer includes a UV absorber, for example belonging to the triazine family or the benzotriazole family. Preferably, the top coating layer also includes a free radical scavenger, which can reduce the risk of the top coating layer turning yellow when exposed to sunlight. The method preferably includes a step of curing, preferably completely curing the top coating layer. During the curing of the top coating layer, it is possible that one or more layers below that are still gelled or partially cured become completely cured. Preferably, the top coating layer is cured with a gallium and / or mercury UV lamp, preferably with both of them.
[0055] In some embodiments, when a matte finish to the surface is desired, it is preferred to cure the topcoat using excimer radiation.
[0056] According to a particular embodiment, at least the topcoat is cured using an electron beam. Electron beam may be preferred because it does not require the presence of a photoinitiator in the topcoat composition. Thus, the topcoat may be easily certified as suitable for contact with food due to the absence of release of a photoinitiator.
[0057] According to an alternative preferred embodiment, the top coating layer comprises polymeric photoinitiators. Polymeric photoinitiators have the characteristic that they are able to crosslink with the polymer matrix of the top coating layer, thereby preventing their release. Therefore, the top layer can easily be proven to be suitable for contact with food.
[0058] Preferably, after curing the topcoat shows a degree of polymerization of at least 90%, even more preferably 94% or more.
[0059] The top coat may be applied using roller coating, reverse roller coating, curtain coating or spray coating. In a preferred embodiment, the top coat may be applied using roller coating or reverse roller coating, wherein the latter has been found to provide the best results in terms of gloss. The roller used to apply the top coat may be a hard roller, such as a hard roller having a Shore hardness greater than 40 Shore, preferably 50 Shore. The use of a hard roller for applying the topmost layer provides a smoother surface finish, which may have a higher gloss.
[0060] In some embodiments, the top coat may be applied in an amount between 2 and 10 g / sqm, such as 6 g / sqm.
[0061] Preferably, the topcoat comprises a gloss between 20 and 70, more preferably between 40 and 70, when measured at an angle of 60°.
[0062] According to an important embodiment of the present invention, which may also form its independent aspect, the method may include a step of polishing the protective coating once the protective layer is fully cured. It should be noted that when processing a finishing coating formed by a polymer, final curing is usually the last step of the method. In fact, such materials are very sensitive to scratches and further steps, in particular machining steps, are not recommended. However, the inventors have found that performing a polishing step can unexpectedly lead to improved gloss and improved surface feel, which leads to a more natural and less plastic tactile feedback. In this case, preferably the top coating is thick enough and the polishing step removes about 8 to 10 microns from the top coating. In this case, the top coating is provided in an amount between 10 and 20 g / sqm.
[0063] Specifically, the last polishing step can be performed using an abrasive having a CAMI particle size equal to or greater than 800, preferably between 800 and 10000. In some embodiments, the last polishing step uses at least an abrasive having a CAMI particle size of 10000. For example, in some embodiments, different abrasives are used in the order of the following CAMI particle sizes: 800-2000-3500-6000-10000 in the last polishing step. Alternatively, in the polishing step, different abrasives are used in the order of the following CAMI particle sizes: 6000-10000. The inventors have found that using such fine-grained abrasives, it is possible to obtain a smooth polished surface without leaving visible scratches on the surface. In the case of using multiple abrasives during the last polishing step, each abrasive is cycled for at least 10 cycles. In this way, the effect of each abrasive is substantially evenly distributed on the surface, and residual scratches can be avoided. In some embodiments, the polishing step can result in an increase in glossiness of at least 10 glossiness when measured at 60 °.
[0064] The inventors have found that a final polishing step can be effective in providing the desired finish, also where the protective coating is applied in a single layer. In this case, preferably the single layer is sufficiently thick and the polishing step removes about 8 to 10 microns from the single layer. In this case, the protective coating is provided in an amount between 10 and 20 g / sqm.
[0065] It should also be noted that in alternative embodiments, the protective coating may comprise a heat curable coating, and the step of fully curing the protective coating comprises at least a heating step. In this case, the protective coating comprises a silicone or melamine based resin. Heat curable substances may show improved scratch resistance.
[0066] In some embodiments, the method may include one or more steps of forming a relief on the surface of the decorative element, and / or one or more steps of forming an area with different glossiness. The relief and / or area with different glossiness can be obtained according to a pattern, and even more preferably determined by printing. Preferably, the printing can be obtained by a contactless printing technology, such as digital inkjet printing. For example, the printing is intended to provide a substance that changes the chemical or physical properties of the surface of the decorative element on the surface of the decorative element. Preferably, the substance can be printed in one or more of the primer coating, the bottom coating or the top coating before the corresponding gelation and / or curing and / or one or more. The substance can be (for example) a paint repellent that locally replaces the coating material in and / or on the printed coating, thereby producing a depression at the pattern. Subsequently, the substance is removed, for example, by drying. The substance can be a substance that can locally prevent the coating material printed therein and / or thereon from curing or at least change its curing conditions, so that after curing, the coating at the pattern will be harder or softer than the coating at the area where the substance is not printed. The coating is then treated, e.g. mechanically, to remove uncured or softer areas of the coating, thereby possibly creating depressions with the substance. Examples of such substances may be antioxidants, electron scavengers, cure inhibitors. Alternatively, the substance may cause a local change in the gloss of the coating, e.g. may locally change the crystallization conditions of the coating printed therein and / or thereon.
[0067] In a fourth independent aspect, the present invention may relate to a decorative element comprising a base and a top layer, wherein the base is made of engineered stone, and wherein the top layer comprises a decorative pattern. The decorative element of the fourth independent aspect may comprise the feature of having a viscosity promoter coating between the base and the top layer. It should be noted that the decorative element of the third independent aspect may be obtained by the method of the first, second or third independent aspect, and / or may comprise any of the above mentioned features in combination with any of the preceding independent aspects, in particular with reference to the composition, dimensions and arrangement of the elements forming the decorative element. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] For the purpose of better illustrating the features of the present invention, several preferred embodiments are described below, by way of example and without any limiting nature, with reference to the accompanying drawings, in which:
[0069] Figure 1 is a perspective view of a decorative element according to the present invention;
[0070] Figure 2 Shown on a larger scale along Figure 1 A cross section along line II-II shown in FIG.
[0071] Figure 3 Shown on a larger scale Figure 2 A view of area F3 shown above;
[0072] Figure 4 Shown for manufacturing Figure 1 Some steps in a method of decorating an element;
[0073] Figure 5 A method for manufacturing a Figure 1 Steps in a method of decorating an element;
[0074] Figure 6 A method for manufacturing a Figure 1 Steps in a method of decorating an element. DETAILED DESCRIPTION
[0075] refer to Figure 1 and Figure 2 , shows that the decorative element 1 is in slab form and has a length X of at least 2m, preferably at least 2.5m, for example 3m or more, and a width Y of at least 1m, preferably 1.5m or more. In addition, the decorative element 1 shows a thickness Z of at least 10mm, preferably at least 20mm, for example 30mm.
[0076] The decorative element 1 comprises a substrate 2 and a top layer 3 covering the upper surface of the substrate 2 .
[0077] The substrate 2 is made of engineered stone, wherein the engineered stone comprises an inorganic filler and a cured organic binder that binds the inorganic filler particles together. The inorganic filler is based on silicon dioxide, such as silica or feldspar. The binder is preferably a thermosetting resin, and more specifically an unsaturated polyester resin.
[0078] The decorative element 1 comprises a first decorative pattern 4 and a second decorative pattern 5. The first decorative pattern 4 and the second decorative pattern 5 are both visible from the top surface of the decorative element itself. The upper surface of the decorative element shows a glossiness between 20 and 50, more preferably between 25 and 40, measured at an angle of 60°.
[0079] The first decorative pattern 4 is a printed pattern present in the top layer 3, whereas the second decorative pattern is a three-dimensional decoration present in the entire thickness of the substrate 2. The first decorative pattern 4 has a higher resolution than the second decorative pattern 5.
[0080] like Figure 3 As shown, the top layer includes, from bottom to top, an adhesion promoting coating 6, a primer coating 7, a decorative layer 8 and a protective coating 9.
[0081] The viscosity-promoting coating 6 comprises a silane-based viscosity promoter. The viscosity-promoting coating 6 is transparent.
[0082] The primer coating 7 is acrylate-based and comprises a UV-curing substance. The primer coating 7 is transparent.
[0083] The decoration layer 8 is formed by the inkjet printing ink that forms the first decoration pattern 4. The ink that forms the decoration layer includes a UV curable adhesive and an inorganic pigment.
[0084] The protective coating 9 is acrylate based and comprises a UV curing substance. The protective coating 9 is transparent.
[0085] Figure 4 According to the present invention, a method for manufacturing Figure 1 Some steps in a method of decorating an element.
[0086] In step S1, a mixture 10 is provided into a mold 15 for manufacturing a substrate 2. The mixture 10 contains an inorganic filler and a binder.
[0087] The filler consists of a combination of powders and granules, for example the combination comprises at least 60 wt% of grains and / or granules and between 20 and 35 wt% of powder form, wherein for example the granules have a particle size distribution between 0.1 and 6.5 mm and the powder has an average particle size of less than 45 μm, preferably less than 20 μm. The filler is preferably at least 80%, preferably greater than 85%, and more preferably greater than 90% by weight of the mixture.
[0088] The binder is in powder form and forms up to 10% by weight of the mixture.
[0089] The mixture 10 may also contain additives such as coupling agents, catalysts or cross-linking agents.
[0090] In step S1, the mixture 10 is deposited on the first belt 12 from the hopper 11. The feeder 13 feeds the first colorant group 14 to the mixture 10 on the first belt 12. Due to the advancement of the first belt 12, the mixture 10 having the first colorant 14 falls into the mold 15 provided on the second belt 16, which is provided below the first belt 12. Due to this falling, the first colorant 14 is randomly distributed in the mixture 10 in the mold 15.
[0091] Once the mixture 10 is in the mold 15, the robot 17 delivers the second colorant set 18 according to a predetermined pattern into the mixture 10. The pattern obtained by the combination of the first colorant set 14 and the second colorant set 18 substantially forms the second decorative pattern 5.
[0092] The mixture 10 in the mold 15 advances to a compacting station 19 for compacting step S2 along an advancing direction A. The compacting station 19 comprises a vibration unit 20 and a vacuum unit 21 for applying vibration and vacuum to the mixture in the mold 15, which results in compaction of the mixture.
[0093] The mixture 10, still in the mold, is then conveyed to a curing station 22, where the adhesive is cured in a curing step S3. The curing of the adhesive is activated at a temperature below 200° C. and then continues as an exothermic reaction.
[0094] After the curing step S3 , the substrate 2 of engineered stone obtained, which is now a cementitious material with a porosity of less than 0.2%, is then removed from the mould 15 and transported to multiple machining stations for finishing operations on the substrate 2 .
[0095] In step S4, the substrate 2 is calibrated to make at least the upper surface of the substrate flat. Subsequently, in step S5, the substrate 2 is corrected so that the substrate finally reaches the desired final size. It should be noted that steps S4 and S5 can be reversed.
[0096] Subsequently, in a polishing step S6, at least the upper surface of the substrate is mechanically treated. The polishing step S6 is performed using an abrasive having a CAMI grit number between 300 and 600 grit, preferably 400 grit.
[0097] Then, the substrate 2 is moved to the first coating station 23 for applying the viscosity promoter coating 6 in the first coating step S7. The first coating station 23 comprises one or more coating rollers 24 and a hot air blower 25 for drying the viscosity promoter coating. Preferably, the viscosity promoter coating is applied in an amount of 40 g / sqm and in a water-based solution or suspension. Drying is performed at 50°C.
[0098] Then, the substrate 2 is moved to the second coating station 26 for applying the primer coating 7 in the second coating step S8. The second coating station 26 includes one or more coating rollers 27 and one or more gallium UV lamps 28 for gelation of the primer coating 7. Preferably, the primer coating 7 is applied in an amount of 6 g / sqm using a soft roller 25 with a hardness of 26 Shore. After application, the primer coating 7 is gelled using the gallium UV lamp 28.
[0099] Then, in the printing step S9, the substrate 2 is moved to the printing station 29 for printing the first decorative pattern 4 to form the decorative layer 8. The printing station includes a single-pass inkjet printer 30 and a UV LED 31. The printer 30 is configured to print at least 4 inks, cyan, magenta, yellow and black, and may add one or more special colors. The ink is a UV curable pigment ink. The pigment is an inorganic ink. After printing, the ink is gelled using a UV LED 31.
[0100] Then, in the third coating step S10, the substrate 2 is moved to the third coating station 32 for applying a primer layer forming a protective coating layer 9. The third coating station 32 includes one or more coating rollers 27, one or more gallium UV lamps 28 and one or more mercury HG UV lamps 33 for curing the primer layer. The primer layer is applied in an amount of 50 g / sqm using a soft roller 25 having a hardness of 26 Shores. After application, the primer layer is completely cured using the gallium UV lamp 28 and the mercury HG UV lamp 33.
[0101] After the base coat is fully cured, the substrate 2 is then moved to the grinding station 34 to perform the grinding step S11. In the example, the grinding station 34 is configured to use a variety of abrasives 35, 36, 37 and 38 to grind the base coat surface. The first abrasive 35 has a CAMI particle size number of 320 grits and moves in a direction perpendicular to the advancing direction A. The second abrasive 36 has a CAMI particle size number of 500 grits and moves in a direction substantially parallel to the advancing direction A. The third abrasive 37 shows a CAMI particle size number of 600 grits and moves in a direction perpendicular to the advancing direction A. The fourth abrasive 38 shows a CAMI particle size number of 800 grits and moves in a direction substantially parallel to the advancing direction A.
[0102] Then, in the fourth coating step S12, the substrate 2 is moved to the fourth coating station 39 for applying a top coating forming the protective coating 9. The fourth coating station 39 includes one or more coating rollers 40, one or more gallium UV lamps 28 and one or more mercury HG UV lamps 33 for curing the top coating. The top coating is applied in an amount of 6 g / sqm using a hard roller 40 with a hardness of 50 Shore. After application, the top coating is completely cured using the gallium UV lamp 28 and the mercury HG UV lamp 33, and the decorative element is finally ready for packaging or sale.
[0103] Figure 5 Another embodiment is shown, which is similar to Figure 4The difference of the embodiment of the present invention is that the embodiment also includes a final polishing step S13 after the protective layer is fully cured. The final polishing step is carried out at a polishing station 41, and in this embodiment, the polishing station 41 is configured to use a variety of abrasives 42, 43, 44 and 45 to polish the protective coating 9. The first abrasive 42 has a CAMI particle size number of 800 grit and moves in a direction perpendicular to the advancing direction A. The second abrasive 43 has a CAMI particle size number of 3500 grit and moves in a direction substantially parallel to the advancing direction A. The third abrasive 44 shows a CAMI particle size number of 6000 grit and moves in a direction perpendicular to the advancing direction A. The fourth abrasive 45 shows a CAMI particle size number of 10000 grit and moves in a direction substantially parallel to the advancing direction A. Each abrasive is performed at least 10 cycles. In this case, it is preferred that the top coating is thick enough, and the polishing step removes about 8 to 10 microns from the top coating. In this case, the top coating is provided in an amount between 10 and 20g / sqm.
[0104] Figure 6 Another embodiment is shown, which is similar to Figure 5 The embodiment of is different in that the protective coating 9 is applied as a single layer in step S10 and then finally polished in step S13.
[0105] The invention is in no way limited to the embodiments described above, but this decorative element and its manufacturing method can be realized according to different variants without departing from the scope of the invention.
[0106] In addition, it is apparent from the description that the present invention relates to one or more of the items listed below:
[0107] 1. A method for manufacturing a decorative element, the decorative element comprising a base and a top layer, wherein the base is made of engineered stone and wherein the top layer comprises a decorative pattern, the method comprising the following steps:
[0108] - providing a mixture comprising at least an inorganic filler and a binder;
[0109] - compacting the mixture;
[0110] - curing the adhesive to obtain a substrate;
[0111] And wherein the method comprises the step of inkjet printing a first decorative pattern on at least the top surface of the substrate.
[0112] 2. The method according to item 1, wherein the decorative element is in the form of a plate or a plate blank.
[0113] 3. The method according to item 2, wherein the slab has a length of at least 2 m, preferably at least 2.5 m, for example 3 m or more, and a width of at least 1 m, preferably 1.5 m or more.
[0114] 4. Method according to item 2 or 3, wherein the slab shows a thickness of at least 10 mm, preferably at least 20 mm, for example 30 mm.
[0115] 5. The method according to any one of the above items, wherein the inorganic filler comprises a mineral material, such as any kind of stone, sand, silicon mineral material, such as quartz, silica sand, clay, feldspar, cristobalite, granite, talc or calcium mineral material, such as calcium carbonate, marble, gypsum.
[0116] 6. The method according to any one of the above items, wherein the inorganic filler may include ceramics, glass, metals and other inorganic materials, such as recycled materials.
[0117] 7. The method according to any one of the above items, wherein the majority, ie at least 50% by weight, of the filler, and more preferably mainly consists of an inorganic material based on silicon (Si).
[0118] 8. The method according to any one of the above items, wherein the filler may be in the form of powder, granules, chips, pellets, aggregates or any other particulate form, although granules and powders are preferred.
[0119] 9. The method according to any of the preceding items, wherein the filler is at least partially in the form of a powder having an average particle size of less than 45 μm, preferably less than 20 μm.
[0120] 10. The method according to any of the above items, wherein the filler is at least partially in the form of aggregates, granules and / or particles with a particle size distribution between 0.1 and 6.5 mm, preferably between 0.1 and 2 mm, between 0.1 and 0.7 mm.
[0121] 11. A method according to any one of the above items, wherein the filler consists of a combination of powders and granules, for example the combination may contain at least 60 wt% granules and / or particles and between 20 and 35 wt% powder form, wherein (for example) the particles have a particle size distribution between 0.1 and 6.5 mm, and the powder has an average particle size of less than 45 μm, preferably less than 20 μm.
[0122] 12. The method according to any of the above items, wherein the filler is preferably at least 80%, preferably greater than 85%, and more preferably greater than 90% by weight of the mixture.
[0123] 13. The method according to any one of the preceding clauses, wherein the binder is a curable substance configured to cure so as to bond the particles of the filler together.
[0124] 14. The method according to any of the preceding items, wherein the binder comprises, preferably consists essentially of, a polyester resin, preferably an unsaturated polyester resin.
[0125] 15. The method according to any of the above items, wherein the binder is preferably less than 20%, preferably less than 15%, and more preferably less than 10% by weight of the mixture.
[0126] 16. The method according to any of the above items, wherein the mixture comprises additives, such as coupling agents, catalysts or agents to activate or accelerate the hardening of the adhesive, and / or temporary binders, such as glue or thermoplastic resins to temporarily bind the stone or stone-like material.
[0127] 17. The method according to any one of the above items, wherein the mixture comprises at least a silane-based coupling agent.
[0128] 18. The method according to any one of the preceding items, wherein the mixture comprises one or more colorants.
[0129] 19. The method according to item 18, wherein the colorant may be in the form of a dye or a pigment.
[0130] 20. The method according to item 19, wherein the pigment can be organic or inorganic, the latter being even more preferred since UV resistance is further improved.
[0131] 21. The method according to any of the preceding items, wherein the mixture is provided into a mold.
[0132] 22. The method according to item 21, wherein a first colorant or a first group of colorants is added to the mixture before and / or during the step of providing the mixture into a mold.
[0133] 23. A method according to item 22, wherein the first colorant or first colorant group is uniformly distributed in the substrate to provide the basic color of the engineered stone, and / or wherein the first colorant or first colorant group is distributed according to a random pattern, such as a random texture effect or a dotted effect.
[0134] 24. Method according to any of items 21 to 23, wherein during and / or after the step of providing the mixture into a mold, a second colorant or a second set of colorants can be added in such a way that a second decorative pattern of the decorative element is formed.
[0135] 25. The method according to item 24, wherein a second colorant or a second set of colorants is provided according to a predetermined pattern, such as a texture effect imitating the veins or scales of marble, granite or any natural stone.
[0136] 26. Method according to item 25, wherein the random pattern of the first colorant or first group of colorants, or the predetermined pattern of the second colorant or second group of colorants, or preferably a combination thereof, forms a second decorative pattern of the decorative element.
[0137] 27. The method according to item 26, wherein the second decorative pattern is present in the substrate, and in particular is present over the entire thickness of the substrate.
[0138] 28. The method according to any one of the preceding items, wherein the method comprises the step of compacting the mixture.
[0139] 29. The method according to item 28, wherein the compacting step is performed by applying both vacuum and vibration.
[0140] 30. The method according to any of the preceding items, wherein curing of the adhesive can be achieved by radiation, heat, chemical curing or other suitable techniques.
[0141] 31. The method according to any of the preceding items, wherein curing of the adhesive is carried out at a temperature below 500°C, such as below 200°C, such as at room temperature.
[0142] 32. The method according to any of the preceding items, wherein the curing step is heat activated and proceeds in an exothermic reaction.
[0143] 33. The method of clause 32, wherein activation of curing of the adhesive can occur at a temperature below 100°C.
[0144] 34. The method according to any of the preceding items, wherein after curing, the engineered stone comprises a porosity of less than 1% by volume, preferably less than 0.5% by volume, even more preferably less than 0.2% by volume.
[0145] 35. The method according to any one of the preceding items, wherein after curing, the method comprises a calibration step and / or a square-up step.
[0146] 36. The method according to any of the preceding items, wherein the method comprises a polishing step adapted to provide a desired texture to the upper surface of the substrate.
[0147] 37. The method according to item 36, wherein the polishing step is performed using an abrasive having a CAMI grit number between 300 and 600 grit, preferably 400 grit.
[0148] 38. A method according to any one of the preceding items, wherein it comprises the step of applying a viscosity promoter coating on the upper surface of the substrate.
[0149] 39. The method of item 38, wherein the viscosity promoter coating comprises a silane-based substance.
[0150] 40. A method according to item 38 or 39, wherein the viscosity promoter coating is applied at a wet amount of between 20 and 60 g / sqm, preferably 40 g / sqm.
[0151] 41. A method according to any one of items 38 or 40, wherein the viscosity promoter coating is a water-based substance and the method further comprises the step of drying the viscosity promoter coating.
[0152] 42. A method according to item 41, wherein the viscosity promoter coating comprises a dry matter to water content ratio of between 1:6 and 1:2, such as 1:4, before drying.
[0153] 43. The method according to item 41 or 42, wherein the drying step can be performed using air blowing and / or IR radiation.
[0154] 44. The method according to any one of the preceding items, wherein the method comprises applying a primer coating on the upper surface of the substrate.
[0155] 45. The method according to item 44, wherein the primer coating is transparent or translucent.
[0156] 46. The method according to item 44 or 45, wherein the primer coating is a radiation curable material, preferably a UV curable material.
[0157] 47. A method according to any one of items 44 to 46, wherein the primer coating is acrylate based, for example an acrylate based oligomer, such as epoxy acrylate, polyester acrylate, polyurethane acrylate or an acrylate based monomer, preferably having a functionality of 1 to 6.
[0158] 48. The method according to any one of items 44 to 47, wherein the primer coating comprises a UV absorber, for example belonging to the triazine or benzotriazole family.
[0159] 49. The method according to any one of items 44 or 48, wherein the method comprises the step of gelling the primer coating, preferably using a gallium (Ga) UV lamp.
[0160] 50. The method according to any one of the preceding items, wherein the printing step is performed to obtain a printed pattern with a resolution of up to 360 dpi.
[0161] 51. A method according to any one of the preceding items, wherein the printed pattern is applied to predetermined points, preferably in a fixed relationship.
[0162] 52. A method according to any one of the preceding items, wherein the method comprises the steps of identifying a second pattern present on the substrate and selecting a pattern to be printed based on said identification.
[0163] 53. The method according to any of the above items, wherein the ink is a pigmented ink.
[0164] 54. The method according to item 53, wherein the pigment can be organic or inorganic.
[0165] 55. The method according to any of the above items, wherein for black ink, the preferred pigment is carbon black.
[0166] 56. The method according to any of the above items, wherein the ink is a UV curable ink.
[0167] 57. The method according to item 56, wherein the method preferably comprises the step of curing the printed ink, preferably using LED UV lamps.
[0168] 58. The method according to any of the preceding items, wherein the ink is transparent or translucent, such that a second decorative pattern present in the substrate is visible through the ink.
[0169] 59. The method according to any one of the preceding items, wherein the method comprises the step of providing a protective coating on the printed pattern.
[0170] 60. The method of clause 59, wherein the protective coating comprises a primer layer applied directly on top of the printed pattern and a top coating layer provided over the primer layer.
[0171] 61. The method according to item 60, wherein the base coating is transparent or translucent.
[0172] 62. The method according to item 60 or 61, wherein the primer layer is preferably acrylate-based, for example an acrylate-based oligomer, such as epoxy acrylate, polyester acrylate, polyurethane acrylate or an acrylate-based monomer, preferably with a functionality of 1 to 6.
[0173] 63. The method according to any one of items 60 to 62, wherein the base coating comprises scratch resistant additives, such as hard particles.
[0174] 64. The method according to any one of items 60 to 63, wherein the primer layer comprises a UV absorber, for example belonging to the triazine family or the benzotriazole family.
[0175] 65. A method according to any one of items 60 to 64, wherein the base coat is applied in an amount of between 5 and 75 g / sqm, preferably between 5 and 60 g / sqm, for example 6 or 60 g / sqm.
[0176] 66. A method according to any one of items 60 to 65, wherein the method comprises a step of at least partially, possibly completely, curing the base coating prior to the step of providing the top coating.
[0177] 67. The method of any one of items 60 to 66, wherein the primer layer is cured using a gallium UV lamp.
[0178] 68. A method according to item 66 or 67, wherein after the primer is applied and at least partially cured, preferably fully cured, the method comprises a step of sanding the primer; preferably, in this case, the amount of primer is at least 35 g / sqm.
[0179] 69. The method according to any one of items 60 to 68, wherein the top coating is transparent or translucent.
[0180] 70. A method according to any one of items 60 to 69, wherein the top coating is preferably acrylate based, for example an acrylate based oligomer, such as epoxy acrylate, polyester acrylate, polyurethane acrylate or an acrylate based monomer, preferably having a functionality of 1 to 6.
[0181] 71. The method according to any one of items 60 to 70, wherein the top coating comprises a UV absorber, for example belonging to the triazine family or the benzotriazole family.
[0182] 72. A method according to any one of items 60 to 71, wherein the top coating comprises a free radical scavenger.
[0183] 73. A method according to any one of items 60 to 72, wherein the top coating is applied in an amount between 2 and 10 g / sqm, for example 6 g / sqm, and / or wherein the top coating is applied in an amount between 10 and 20 g / sqm.
[0184] 74. A method according to any one of items 60 to 73, wherein the method comprises the step of at least partially, preferably completely, curing the topcoat.
[0185] 75. The method according to item 74, wherein the base coating is finally cured during the curing of the top coating.
[0186] 76. The method according to item 74 or 75, wherein the top coating is cured with gallium and / or mercury UV lamps, preferably with both.
[0187] 77. The method according to any one of items 74 to 75, wherein the top coating is cured using excimer radiation.
[0188] 78. The method of any one of items 74 to 75, wherein the top coating is cured using an electron beam.
[0189] 79. The method of any one of items 74 to 77, wherein the top coating comprises a polymeric photoinitiator.
[0190] 80. The method according to any one of items 74 to 79, wherein after curing the topcoat shows a degree of polymerization of at least 90%, even more preferably 94% or more.
[0191] 81. The method according to any one of items 60 to 80, wherein the base coating and the top coating can be applied using roller coating, reverse roller coating, curtain coating or spray coating.
[0192] 82. The method of item 81, wherein the base coat is applied using roller coating and the top coat is applied using reverse roller coating.
[0193] 83. Method according to any of the preceding items, comprising one or more steps of forming a relief on the surface of the decorative element, and / or one or more steps of forming areas with different glossiness.
[0194] 84. Method according to item 83, wherein the reliefs and / or areas with different glossiness can be obtained according to a pattern, even more preferably determined by printing.
[0195] 85. Whether or not according to any of the above items, a method for manufacturing a decorative element, the decorative element comprising a base and a top layer, wherein the base is made of engineered stone, and wherein the top layer comprises a decorative pattern, the method comprising the steps of:
[0196] - providing a mixture comprising at least an inorganic filler and a binder;
[0197] - compacting the mixture;
[0198] - curing the adhesive to obtain a substrate;
[0199] - wherein the method comprises the step of inkjet printing a first decorative pattern on at least the top surface of the substrate;
[0200] wherein the method comprises the step of providing a protective coating on the printed pattern, wherein the protective coating comprises a curable substance, wherein the method comprises the step of fully curing the protective coating, and wherein the method comprises the step of polishing the protective coating.
[0201] 86. The method according to item 85, wherein the polishing step is performed using an abrasive having a CAMI grit number between 800 and 10,000.
[0202] 87. The method according to item 85 or 86, wherein in the polishing step, different abrasives are used in the following order of CAMI grit numbers: 800-2000-3500-6000-10000.
[0203] 88. The method according to item 85 or 86, wherein in the polishing step, different abrasives are used in the order of the following CAMI grit numbers: 6000-10000.
[0204] 89. The method of item 87 or 88, wherein at least 10 cycles are performed with each abrasive.
[0205] 90. The method according to any one of the above items, wherein the polishing step is performed using an abrasive with a CAMI grit number equal to or greater than 800.
[0206] 91. The method according to any of the above items, wherein the polishing step results in an increase in gloss of at least 10 gloss levels when measured at 60°.
[0207] 92. The method according to any of the preceding items, wherein the protective coating is applied in a single layer.
[0208] 93. A method according to item 92, wherein the protective coating is provided in an amount between 10 and 20 g / sqm.
[0209] 94. The method according to any of the above items, wherein the protective coating comprises a primer layer applied directly on top of the printed pattern and a top coating layer provided over the primer layer.
[0210] 95. A method according to item 94, wherein between applying the primer layer and applying the top coat, the method comprises a step of sanding the primer layer; preferably, in this case, the primer layer is in an amount of at least 35 g / sqm.
[0211] 96. A method according to item 94 or 95, wherein the base coating and / or the top coating are provided in an amount between 6 and 8 g / sqm respectively; and / or wherein the top coating is provided in an amount between 10 and 20 g / sqm.
[0212] 97. A method according to any one of the preceding clauses, wherein after the step of curing the adhesive, the method comprises a calibration step.
[0213] 98. A method according to item 97, wherein immediately after the calibration step, the method includes the step of applying a viscosity promoter coating to the upper surface of the substrate.
[0214] 99. A method according to item 98, wherein no surface mechanical treatment operation is performed between the calibration and the application of the viscosity promoter coating.
[0215] 100. The method according to item 99, wherein the surface mechanical treatment operation comprises polishing and / or grinding.
[0216] 101. A method according to any one of items 98 to 100, wherein the viscosity promoter coating comprises a silane-based material.
[0217] 102. The method according to any one of the above items, wherein the protective coating is a radiation curable coating, and the step of fully curing the protective coating comprises UV or EB (electron beam) curing.
[0218] 103. The method according to any one of the above items, wherein the protective coating is a heat-curable coating, and the step of fully curing the protective coating comprises at least a heating step.
[0219] 104. The method of item 104, wherein the protective coating comprises a silicone or melamine-based resin.
[0220] 105. A decorative element comprising a base and a top layer, wherein the base is made of engineered stone and wherein the top layer comprises a decorative pattern, wherein a viscosity promoter coating is included between the base and the top layer.
[0221] 106. The decorative element according to item 105, wherein the viscosity promoter coating is silane-based.
[0222] 107. Decorative element according to item 105 or 106, wherein the top layer comprises a primer coating and / or a protective coating.
Claims
1. A method for manufacturing a decorative element (1), the decorative element (1) comprising a base (2) and a top layer (3), wherein the base (2) is made of engineered stone and wherein the top layer (3) comprises a decorative pattern (4), the method comprising the following steps: - providing (S1) a mixture (10) comprising at least an inorganic filler and a binder; - compacting (S2) the mixture; - curing (S3) the adhesive to obtain the substrate (2); The method comprises the step of inkjet printing a first decorative pattern (4) on at least the top surface of the substrate (2); The method comprises the step of providing a protective coating (9) on the printed first decorative pattern (4), wherein the protective coating (9) comprises a curable substance, wherein the method comprises the step of fully curing the protective coating, and wherein the method comprises the step of polishing the protective coating (9) (S13).
2. The method according to claim 1, wherein the polishing step (S13) is performed using an abrasive having a CAMI grit number between 800 and 10000.
3. The method according to claim 1 or 2, wherein in the polishing step (S13), different abrasives are used in the following order of CAMI grit numbers: 800-2000-3500-6000-10000.
4. The method of claim 3, wherein at least 10 cycles are performed with each abrasive.
5. The method according to any one of the preceding claims, wherein in the polishing step (S13), different abrasives are used in the following order of CAMI grit numbers: 6000-10000.
6. The method according to any one of the preceding claims, wherein the polishing step (S13) is performed using an abrasive having a CAMI grit number equal to or greater than 800.
7. The method according to any one of the preceding claims, wherein the polishing step (S13) results in an increase in gloss of at least 10 gloss levels when measured at 60°.
8. Method according to any of the preceding claims, wherein the protective coating (9) is applied in a single layer.
9. The method according to claim 8, wherein the protective coating (9) is provided in an amount of 6 and 20 g / sqm, more preferably 10 and 20 g / sqm.
10. The method according to any one of claims 1 to 7, wherein the protective coating (9) comprises a primer layer applied (S10) just on top of the printed decorative pattern (4) and a top coating layer provided (S12) above the primer layer.
11. The method according to claim 10, wherein between the application of the primer layer (S10) and the application of the top layer (S12), the method comprises a step of grinding the primer layer (S11).
12. The method of claim 10, wherein the primer coating is provided in an amount of at least 35 g / sqm and the protective coating is provided in an amount between 10 and 20 g / sqm.
13. The method according to any one of the preceding claims, wherein after the step of curing (S3) the adhesive, the method comprises a calibration step (S4).
14. The method according to claim 13, wherein, immediately after the calibration step (S4), the method comprises the step of applying (S6) a viscosity promoter coating (6) on the upper surface of the substrate (2).
15. Method according to claim 14, wherein between calibration (S4) and application (S6) of the viscosity promoter coating, no surface mechanical treatment operation is performed.
16. The method according to claim 15, wherein the surface mechanical treatment operation comprises polishing and / or grinding.
17. The method according to claim 14, wherein the viscosity promoter coating (6) comprises a silane-based substance.
18. The method according to any one of the preceding claims, wherein the protective coating (9) is a radiation curable coating and the step of fully curing the protective coating comprises UV or EB (electron beam) curing.
19. The method according to any one of claims 1 to 17, wherein the protective coating (9) is a heat-curable coating and the step of fully curing the protective coating comprises at least a heating step.
20. The method according to claim 19, wherein the protective coating (9) comprises silicone or melamine based resin.
21. A method for manufacturing a decorative element (1), said decorative element (1) comprising a base (2) and a top layer (3), wherein said base (2) is made of engineered stone and wherein said top layer (3) comprises a decorative pattern (4), said method comprising the following steps: - providing (S1) a mixture (10) comprising at least an inorganic filler and a binder; - compacting (S2) the mixture; - curing (S3) the adhesive to obtain the substrate; - inkjet printing a first decorative pattern (4) on at least the top surface of the cured substrate (3); Wherein before the inkjet printing step, the method comprises a step (S7) of providing a viscosity promoter coating (6) on the surface of the substrate (2).
22. The method according to claim 21, wherein the viscosity promoter coating (6) comprises a silane-based substance.
23. A method according to claim 21 or 22, wherein the viscosity promoter coating (6) is applied at a wet weight of between 20 and 60 g / sqm, preferably 40 g / sqm.
24. The method according to any one of claims 21 to 23, wherein the viscosity promoter coating (6) is a water-based substance and the method further comprises the step of drying the viscosity promoter coating (6).
25. The method according to claim 24, wherein the viscosity promoter coating (6) comprises a dry matter to water content of between 1:6 and 1:2, such as 1:4, before drying.
26. The method according to claim 24 or 25, wherein the drying step can be performed using air blowing and / or IR radiation.
27. A method according to any one of claims 21 to 26, wherein the method comprises applying a primer coating (7) over the viscosity promoter coating (6).
28. The method according to claim 27, wherein the primer coating (7) is transparent or translucent.
29. The method according to claim 27 or 28, wherein the primer coating (7) is a radiation-curable substance, preferably a UV-curable substance.
30. The method of claim 29, wherein the method comprises the step of gelling the primer coating, preferably using a Gallium (Ga) UV lamp.
31. A method according to any one of claims 27 to 30, wherein the primer coating (7) is acrylate based, for example an acrylate based oligomer, such as epoxy acrylate, polyester acrylate, polyurethane acrylate or an acrylate based monomer, preferably having a functionality of 1 to 6.
32. The method according to any one of claims 27 to 31, wherein the primer coating (7) comprises a UV absorber, for example belonging to the triazine or benzotriazole family.
33. Method according to any one of claims 21 to 26, wherein the method comprises applying a protective coating (9) on the first decorative pattern.
Citation Information
Patent Citations
A process for the manufacturing of slabs or blocks of conglomerate of stone granulate and polyester resin
WO2007138529A2
Method and apparatus for manufacturing slabs with veined effect
WO2009010406A2
Programmable station and plant for the production of plates with chromatic effects
WO2016113652A1
Method for manufacturing an engineered stone and an engineered stone
WO2019070621A2